Activity of the LMP1 gene promoter in Epstein–Barr virus-transformed cell lines is modulated by sequence variations in the promoter-proximal CRE site - Jansson, Ann; Johansson, Pegah; Li, Susann; Rymo, Lars (Journal of General Virology, 2007)
The Epstein–Barr virus (EBV)-encoded tumour-associated latent membrane protein 1 (LMP1) gene expression is transactivated by EBV nuclear antigen 2 (EBNA2) in human B cells. We have previously identified a cyclic AMP-responsive element (CRE) in the B95-8 LMP1 promoter that is essential for transcription activation. Sequencing of LMP1 promoter in the P3HR1-derived EREB2.5 cell line revealed 25 single base pair substitutions in comparison to the B95-8 virus, one of them localized in the CRE element. Sequence variations in this element have been identified in several EBV isolates of both African and Asian origins. The effect of the P3HR1 CRE site variation on binding of factors to the LMP1 promoter sequence (LRS) and promoter activation was investigated with electrophoreticmobility-shift assays and reporter gene transfection assays. ATF1 and CREB1 transcription factors bound with reduced efficiency to the P3HR1 variant and below the detection level to the other tested variants. Accordingly, reporter plasmids carrying the P3HR1 CRE sequence in a B95-8 LRS context displayed 50 % lower activity in all tested cell lines. The impaired ability to activate transcription caused by the C to A substitution in CRE was not apparent when the mutated site was placed in a P3HR1 LRS context and the reporter transfected into Jijoye cells, most likely as a consequence of the other base pair substitutions in P3HR1 LRS. Overall, our results suggest that the mutations in the LRS CRE site have been conserved to adjust LMP1 expression to levels that favour cell survival in certain cellular and environmental contexts.